Answer:
2.74 x 10 square root of 3
Step-by-step explanation:
hope this helps give brainliest
Answer:
x=6
Step-by-step explanation:
Answer:
d)
Step-by-step explanation:
<u><em>Explanation</em></u>
Given expression
= ![\frac{(4g^{3} h^{2}k^{4} )^{3} }{8g^{3}h^{2} } - (h^{5} k^{3} )^{5}](https://tex.z-dn.net/?f=%5Cfrac%7B%284g%5E%7B3%7D%20h%5E%7B2%7Dk%5E%7B4%7D%20%29%5E%7B3%7D%20%20%7D%7B8g%5E%7B3%7Dh%5E%7B2%7D%20%20%7D%20-%20%28h%5E%7B5%7D%20k%5E%7B3%7D%20%29%5E%7B5%7D)
By using
(ab)ⁿ = aⁿbⁿ
![\frac{a^{m} }{a^{n} } = a^{m-n}](https://tex.z-dn.net/?f=%5Cfrac%7Ba%5E%7Bm%7D%20%7D%7Ba%5E%7Bn%7D%20%7D%20%3D%20a%5E%7Bm-n%7D)
= ![\frac{(4)^{3} g^{9} h^{6}k^{12} ) }{8g^{3}h^{2} } - (h^{5} k^{3} )^{5}](https://tex.z-dn.net/?f=%5Cfrac%7B%284%29%5E%7B3%7D%20g%5E%7B9%7D%20h%5E%7B6%7Dk%5E%7B12%7D%20%29%20%20%7D%7B8g%5E%7B3%7Dh%5E%7B2%7D%20%20%7D%20-%20%28h%5E%7B5%7D%20k%5E%7B3%7D%20%29%5E%7B5%7D)
After simplification , we get
![= 8g^{9}g^{-3} h^{6} h^{-2} k^{12} - (h^{5} k^{3} )^{5}](https://tex.z-dn.net/?f=%3D%208g%5E%7B9%7Dg%5E%7B-3%7D%20h%5E%7B6%7D%20h%5E%7B-2%7D%20k%5E%7B12%7D%20%20-%20%28h%5E%7B5%7D%20k%5E%7B3%7D%20%29%5E%7B5%7D)
![= 8g^{9-3}h^{6-2} k^{12} - (h^{5} k^{3} )^{5}](https://tex.z-dn.net/?f=%3D%208g%5E%7B9-3%7Dh%5E%7B6-2%7D%20%20k%5E%7B12%7D%20%20-%20%28h%5E%7B5%7D%20k%5E%7B3%7D%20%29%5E%7B5%7D)
Answer:
Option D: 6x-14 is the correct answer.
Step-by-step explanation:
Given that:
Length of the box = L = 2x-2
Width of the box = W = x-5
Perimeter is defined by the sum of length of all sides of the box.
Perimeter of the box = P = 2L + 2W
Perimeter of box = 2(2x-2) + 2(x-5)
Perimeter = 4x-4+2x-10
Perimeter = 6x-14
The perimeter of the box is 6x-14.
Hence,
Option D: 6x-14 is the correct answer.